Specific Energy Absorbed Study of Aluminum (2024-351T) Tubes Alloy under Lateral Crush - Ayad Arab Ghaidan (Tikrit Journal of Engineering Sciences, 2011)
This paper aims to find SEA (Specific Energy Absorber) for lateral crushing (statically) behavior for Aluminum (2024-T351) alloy with difference lengths (10, 20, and 30 mm). An experimental, finite element simulation, and theoretical models present to find force-deformation curves and then find SEA for difference lengths. Experimental results more agreements with finite elements simulation and theoretical when length of tubes is increase for load deformation curve, because when the length increases the plastic region increase with initial plastic collapse load (Pc). The experimental, ANSYS simulation and theoretical results have plotted and it has seen that the theory also underestimates the ANSYS results because in theoretical model, is customary to assume that the material is perfectly plastic; therefore, the finite element simulation might predict the experimental results better than the theoretical one. The results show that light density Aluminum alloy is suitable for SEA